Analisis Penggunaan Media Jari Pada Pembelajaran Matematika Kelas V di Miftahul Huda II - Putri Cahya Novebriani; Istiyati Mahmudah (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Elementary/MI students think that mathematics is a complicated, boring and meaningless subject. Simple learning media that is easy to apply to students in terms of mathematics, this can be done using mathematics learning media. The aim of this research is to evaluate the effectiveness of using mathematics learning media in elementary/MI teaching. This research involved classroom observations, interviews with teachers and school surveys. The results of this research show that the use of mathematics finger media has a positive impact on mathematics learning in class V. Students are more enthusiastic, participate actively and understand mathematical concepts better through the use of this media. Teachers also consider that mathematics finger media is more effective in improving students' mathematical understanding. Therefore, it is recommended to continue to integrate mathematics finger media in mathematics learning in class V at MI Miftahul Huda II.